2018
DOI: 10.1051/0004-6361/201731782
|View full text |Cite
|
Sign up to set email alerts
|

Intriguing X-ray and optical variations of the γ Cassiopeiae analog HD 45314

Abstract: Context. A growing number of Be and Oe stars, named the γ Cas stars, are known for their unusually hard and intense X-ray emission. This emission could either trace accretion by a compact companion or magnetic interaction between the star and its decretion disk. Aims. To test these scenarios, we carried out a detailed optical monitoring of HD 45314, the hottest member of the class of γ Cas stars, along with dedicated X-ray observations on specific dates. Methods. High-resolution optical spectra were taken to m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 90 publications
2
22
0
Order By: Relevance
“…4). A similar correlation was detected for γ Cas (Smith et al 2012), but the opposite trend was found for HD 45314 (Rauw et al 2018). These positive and negative correlations have been theoretically explained by Sigut & Patel (2013) by way of differences in disk inclination (higher inclinations leading to inverse correlations) but also in disk scale heights.…”
Section: Optical and Near-infrared Lines Of π Aqrsupporting
confidence: 73%
“…4). A similar correlation was detected for γ Cas (Smith et al 2012), but the opposite trend was found for HD 45314 (Rauw et al 2018). These positive and negative correlations have been theoretically explained by Sigut & Patel (2013) by way of differences in disk inclination (higher inclinations leading to inverse correlations) but also in disk scale heights.…”
Section: Optical and Near-infrared Lines Of π Aqrsupporting
confidence: 73%
“…Models have considered either a relatively low mass-accretion rate onto a compact companion or magnetic star-disk interactions. Evidence of a correlation between UV/optical and X-ray variations on short timescales (Smith & Robinson 1999;Robinson et al 2002) as well as marked dependencies of the X-ray luminosities on decretion disk density with basically zero delay (Motch et al 2015;Rauw et al 2018) appear to favor the latter scenario. The γ Cas nature of π Aqr (a system with a "normal", not compact, companion near the disk, Nazé et al 2017) further supports an X-ray source located close to the Be star.…”
Section: Introductionmentioning
confidence: 92%
“…In addition to fast X-ray shot-noise like variability, large amplitude modulations on timescales of one hour or more are ubiquitous (Smith et al 2016) and long-term variations linked to the disappearance and building-up of the disk have also been detected (Rauw et al 2018). A correlation between X-ray luminosity and disk density was indeed found by Motch et al (2015) and Rauw et al (2018). The presence of short-term variability was assessed when enough counts were present (see the variability flag in Table 1).…”
Section: γ Cas Analogs: New Detectionsmentioning
confidence: 99%
“…We kept sources displaying log(L X /L BOL ) > −7 and for which no other Xray observation was available. We added sources detected by Exosat-ME in the hard X-ray range but not by ROSAT in the soft band, as was the case of the γ Cas analog HD 45314 (Rauw et al 2013(Rauw et al , 2018. Such a situation suggests that these objects display very hard X-ray emissions hence could have a good chance of being γ Cas analogs, if the Exosat detection was not due to optical/UV loading.…”
Section: Introductionmentioning
confidence: 99%
“…A last target, α Ara, was detected as an X-ray source in the XMM-Newton slew survey, as had been the case of the γ Cas ana-log π Aqr (Nazé et al 2017). The second criterion relies on the presence of an optical peculiarity observed in γ Cas and HD 45314 (Rauw et al 2018): a transition of the Hα line from a classical double-peaked pure emission profile to a socalled shell profile. For steady Be disks, a shell profile is observed when the (equatorial) disk is seen edge-on with respect to our line-of-sight.…”
Section: Introductionmentioning
confidence: 99%